2019
DOI: 10.3390/app9081547
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of a Supercapacitor/Battery Hybrid Power System for a Bulk Carrier

Abstract: Concerns about harmful exhaust emissions from ships have been an issue. Specifically, the emissions at ports are the most serious. This paper introduces a hybrid power system that combines conventional diesel generators with two different energy storage systems (ESSs) (lithium-ion batteries (LIB) and supercapacitors (SC)) focused on port operations of ships. To verify the proposed system, a bulk carrier with four deck cranes is selected as a target ship, and each size (capacity) of LIB and SC is determined bas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(17 citation statements)
references
References 20 publications
0
13
0
4
Order By: Relevance
“…Assuming that this project starts in 2020, a battery capital cost of 250 $/kWh is considered, with a discount rate of 2.4%. The capital cost of supercapacitors is typically 10,000 $/kWh [69], as adopted for example in the case study of [70]. The O&M costs of supercapacitors are generally lower than that of batteries, selecting here 0.1% and 0.45% of the investment, respectively, based on [21].…”
Section: Economic Analysis and Discussionmentioning
confidence: 99%
“…Assuming that this project starts in 2020, a battery capital cost of 250 $/kWh is considered, with a discount rate of 2.4%. The capital cost of supercapacitors is typically 10,000 $/kWh [69], as adopted for example in the case study of [70]. The O&M costs of supercapacitors are generally lower than that of batteries, selecting here 0.1% and 0.45% of the investment, respectively, based on [21].…”
Section: Economic Analysis and Discussionmentioning
confidence: 99%
“…Many different topologies regarding hybrid combinations of the Li-ion battery and SC for EVs have been reported [17] - [19]. However, each of these topologies has their own advantages and limitations.…”
Section: A Power Management Strategy Of Eessmentioning
confidence: 99%
“…However, they have more auxiliary loads than container ships, since they often use deck cranes to load or unload cargo. For this reason, the authors of [17,58] investigated the use of hybrid propulsion and a hybrid power supply on these ships, and concluded that it could be beneficial. The power plant control system would use an Equivalent Energy Minimiztion Strategy (ECMS), to provide the optimal power split between the generator sets and the ESS, but also to switch the electric machine between PTO and PTI mode.…”
Section: Container Shipsmentioning
confidence: 99%